Urinary Tract Injury at Benign Gynecologic Surgery and the Role of Cystoscopy: A Systematic Review and Meta-analysis. Issue 4 (April 2016) - Teeluckdharry, Brahmananda; Gilmour, Donna; Flowerdew, Gordon
Abstract : Obstet Gynecol Surv 2016;71(4):216–217 Most ureteric injuries are caused by gynecologic surgery, with most occurring during procedures for benign diseases.